Perancangan Sistem Daur Ulang Air Limbah dengan Sewage Treatment Plant (STP) untuk Efisiensi Penggunaan Air di Gedung Koperasi - Muhammad Thariq Resmaindra; Rahmat Hidayat (Jurnal Karajata Engineering, 2025)
Koperasi XX Building primarily used water supplied by the regional water company (PDAM) due to restriction on groundwater usage, specifically related to the Groundwater Utilization Permit (SIPA). In line with the commitment to improving water resource efficiency and supporting the Sustainable Development Goals (SDGs) of the UN and Indonesian government, the parent company has set a target to reduce water consumption by 30% by 2030. To address this, this study proposed a recycle sewage treatment plant (STP) system designed to meet water efficiency needs by using treated wastewater for non-potable uses, including toilet flushing, garden irrigation, and parking lot cleaning. This study included civil engineering analyses, such as pump selection and piping design, along with evaluations of water savings, Net Quality Income (NQI), and payback period. A Teral lifting pump (ASVM (N,G) 406-52.2) and 5 cm (2-inch) pipes are used, providing a flow rate of 150 m³/min. A 7 m³ upper tank is used for treated water storage. The project is estimated to cost Rp 582,552,846.10 and will require 39 days for implementation. It is expected to reduce PDAM water usage by 78%, leading to a 63% decrease in water bills. Despite a lengthy payback period of 21 years, this initiative offers significant environmental and sustainability benefits.